SPA TREATMENT OF CHILDREN WITH ENVIRONMENTAL-BURDENED PYELONEPHRITIS ASSOCIATED WITH DISORDERS OF PURINE EXCHANGE - L.N. SHVEDUNOVA; A.S. KAYSINOVA; N.V. EFIMENKO; S.V. DYOMINA; S.A. PACHIN; I.I. GAYDAMAKA (Avicenna Tajik State Medical University, 2019)
Objective: To study the effectiveness of the treatment on the basis of drinking mineral waters, carbon dioxide baths and rational pharmacotherapy in children with environmental burdened chronic pyelonephritis, associated with violations of purine exchange, in the conditions of the Zheleznovodsk resort. Methods: Fifty children with chronic pyelonephritis with an environmental burdened anamnesis of 11-14 years were under observation. The method of simple randomization was formed two groups: control (25 people), which received traditionally accepted treatment at the Zheleznovodsk resort (dietary nutrition, therapeutic gymnastics, internal intake of the little mineralized mineral water of the Smirnov spring, carbon dioxide mineral baths), and the main one (25 people), where children received additional drug therapy with herbal medicine Canefron N. All patients were prescribed: ultrasound examination of the kidneys, clinical and biochemical blood and urine tests. Results: Comparative analysis showed that children of main group had a reduction of pain and dysuric syndromes, and in control group pain syndrome by the end of treatment persisted in 8% of cases, slightly more often preserved dysurian (16%) and asthenonneurotic (16%) syndromes. In children of main group, there was a significant decrease in daily oxaluria (by 39.2%; р<0,01), an increase in the rate of glomerular filtration (by 11.93%), which was statistically significant in relation to the data in control group, where there was only a tendency to improve kidney function. According to the data of the long-term results in children of main group, the number of relapses decreased by 2.9 times (p<0.01), while in patients of control group there was only a tendency to decrease this indicator. Conclusion: Comprehensive balneo- and drug therapy in children with environmental burdened pyelonephritis, associated with purine metabolism disorders, contribute to statistically significant to increase clinical effectiveness, ensures the long-term preservation of the achieved therapeutic effect.